Use of Social Media Among Individuals Who Suffer From Post-Traumatic Stress: A Qualitative Analysis of Narratives. (January 2017) - Salzmann-Erikson, Martin; Hiçdurmaz, Duygu
Suffering from post-traumatic stress impacts and restricts the life situation of the individual on several levels, not least regarding social difficulties. Social media on the Internet facilitate new possibilities for interaction and communication. Earlier research has demonstrated that people use social media to seek support and to discuss health-related issues. The current study aimed to describe how individuals suffering from post-traumatic stress use social media to convey authentic narratives of their daily lives, including illness, and further, to analyze the content of this media use. The data comprised YouTube videos, blogs, and forum discussions. Five categories cover the findings: (a) structure of the narrative, (b) narrating the trauma, (c) restrictions in life, (d) strategies in everyday living, and (e) online interaction. We stress that sharing narratives online facilitates a "verbalizing" of the life conditions of the sufferers and can be used as a self-care activity.